Draft Tenth Five Year Plan 2002-07 and Annual Plan 2002-03 Government of Goa - Planning Commission (Planning Commission, 2002)
Goa, Daman and Diu attained independence on 19th December 1961. After nearly 450 years of colonial Portuguese rule Goa, Daman and Diu formed a Union Territory in democratic India vide the Constitution (Twelfth Amendment) Act, 1962 dated March 27,1962. Goa attained statehood on 30th May 1987 and Daman & Diu formed a separate Union Territory.
Government of Goa, Directorate of Planning, Statistics and Evaluation